Leadership in Action : In Focus--Creativity and Innovation--Good Leadership Demands a Combination of the Two - Nissley, Nick (Center for Creative Leadership, 2007)
Leaders must be concerned with developing, both personally and organizationally, the dual capabilities of creativity and innovation.